Analisis Disiplin Kerja Aparatur Sipil Negara (ASN)(Studi Kasus: bagian Kasubag Umum dan Kepegawaian di Kantor Kecamatan Lekok Kabupaten Pasuruan) - Nafisah, Aniyatun; Khumaidi, Khumaidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the work discipline of State Civil Apparatus (ASN) at the Lekok District Office, considering the importance of discipline in improving the performance of the apparatus and the quality of public services. The research method used is descriptive qualitative, with a focus on collecting and describing detailed data on the level of work discipline. The results of the study indicate that in general, the level of discipline of ASN at the Lekok District Office is quite good, especially in terms of punctual attendance, utilization of working hours, and compliance with home hours and not being absent. Although there are several obstacles such as delays and sudden tasks, this does not significantly affect productivity. This study contributes to the understanding of the dynamics of work discipline in the sub-district government environment and can be the basis for a more effective strategy for developing improvements in apparatus performance. Keywords: ASN Performance, State Apparatus, Work Discipline